IMPLEMENTASI METODE TALAQQI DAN TIKRAR DALAM PEMBELAJARAN TAHFIDZ AL-QUR’AN DI SEKOLAH DASAR ISLAM TERPADU: STUDI KASUS DI SDIT INSAN TELADAN KECAMATAN CILEUNYI, KABUPATEN BANDUNG - Angga Toha Saputra; Delis Sri Maryati (CV. AFDIFAL MAJU BERKAH, 2026)
This study examines the adaptation and implementation of the talaqqi method and tikrar (repetitive memorization technique) in Qur'anic memorization (tahfidz) learning at SDIT Insan Teladan, as well as identifies students' tasmī' performance and the factors influencing its effectiveness. Method: A qualitative case study design was employed. Data were collected through participatory observation, in-depth interviews with tahfidz instructors, and document analysis of students' memorization records. Inductive data analysis involved reduction, display, and conclusion drawing, with triangulation ensuring trustworthiness. Results: The talaqqi method is implemented through direct teacher-student interaction to ensure accurate makhārij al-ḥurūf and tajwīd rules as the memorization foundation. The tikrar approach operates through structured daily and weekly repetition patterns to reinforce retention. Students' tasmī' performance showed notable development through a tiered evaluation system, though outcomes were uneven due to individual learning differences. Key supporting factors include teachers' pedagogical competence and a structured instructional system, while major constraints involve limited instructional time and insufficient murāja'ah (revision) support at home. Implications: This study recommends that Islamic educational institutions integrate systematic long-term murāja'ah programs and strengthen school-parent synergy. Additionally, adapting traditional pedagogical approaches into formal curricula requires more innovative strategies to mitigate student fatigue and optimize long-term memorization retention.